AOB - Acoustic Oceanographic Buoy: concept and feasibility - Jesus, S. M. (2014)
The AOB - Acoustic Oceanographic Buoy is the single node of a network of “smart” buoys for acoustic surveillance, Rapid Environmental Assessment (REA) and underwater communications. The AOB is a lightweight surface buoy with a vertical array of acoustic receivers and temperature sensors to be air dropped or hand deployed from a small boat. The received data is geotime and GPS precisely marked, locally stored and processed by on board dedicated DSP hardware. AOBs can exchange data over a local area network that includes submerged, sea surface (like for instance other AOBs) and air or land located nodes, allowing for the integration of all users in a seamless network. Specific software allows AOB usage in complex tasks such as passive or multistatic acoustic surveillance, acoustic observations for REA oceanographic forecast and model calibration, bottom and water column acoustic inversion, underwater communications and cooperating target tracking. The AOB was successfully deployed in several consecutive days during two Maritime REA sea trials in 2003 (Mediterranean), in 2004 (Atlantic) and for an high-frequency underwater communications experiment during MakaiEX, 2005 (Hawai). Data collected at sea shows that the AOB is a versatile, robust and easy to use tool for a variety of broadband underwater acoustic applications.